EFEKTIFITAS VAKSINASI HUMAN PAPILLOMAVIRUS (HPV) DALAM MENCEGAH KEJADIAN KANKER SERVIKS (REVIEW LITERATUR - Maria Lupita Nena Meo (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Cervical cancer accounts for 8.8% of cancer deaths in Indonesia, making it the second leading cause of cancer deaths. The World Health Organization has recommended the human papillomavirus (HPV) vaccination as a preventive measure against cervical cancer. This review aims to provide an evidence-based summary of the effectiveness of HPV vaccination. Literature study on English-language articles collected from the online database PubMed, Google Scholars, and DOAJ with search keywords "Human Papillomavirus Vaccine" and "Cervical Cancer." The results of the selected articles obtained were five articles published in the last five years. The main findings from all studies consistently report that the incidence of pre-cancer and cervical cancer cases is lower in the female population who received the vaccination than in the female population who have not received the HPV vaccination. Other findings also show that the first dose of HPV vaccination is effectively given at the age of under 20 years and is very effective as a prophylaxis to suppress cervical cancer recurrence. The results of this literature review can be used as a basis for increasing the promotion and awareness of HPV vaccination in women of childbearing age so that it can reduce the incidence of cervical cancer.